2018
DOI: 10.1002/ece3.4332
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and abundance of macro‐invertebrates on abandoned cattle kraals in a semi‐arid savanna

Abstract: Abandoned cattle (Bos taurus) kraals are sources of habitat heterogeneity in dystrophic semi‐arid African savannas with a strong positive effect on soil nutrients and plant productivity. However, little is known regarding how macro‐invertebrate assemblages vary between abandoned kraals and the surrounding savanna matrix. We tested whether herbaceous biomass and basal and aerial covers and soil nutrients have an effect on aboveground and belowground macro‐invertebrate assemblages. Twelve abandoned kraals were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
(119 reference statements)
1
4
0
Order By: Relevance
“…For urban rivers, we should not only consider the potential impact of nutrients on diversity but also consider the coupling relationship between the interactions of various critical environmental factors and the macro-invertebrate community [43]. In our study, we determined the ecological suitability of benthic animals by fitting the responses of critical environmental factors and macro-invertebrates and demonstrated that benthic responses to multiple critical environmental factors were nonlinear, confirming the findings of previous studies [44,45].…”
Section: Single-factor Significance Test Used For Critical Water Qual...supporting
confidence: 86%
“…For urban rivers, we should not only consider the potential impact of nutrients on diversity but also consider the coupling relationship between the interactions of various critical environmental factors and the macro-invertebrate community [43]. In our study, we determined the ecological suitability of benthic animals by fitting the responses of critical environmental factors and macro-invertebrates and demonstrated that benthic responses to multiple critical environmental factors were nonlinear, confirming the findings of previous studies [44,45].…”
Section: Single-factor Significance Test Used For Critical Water Qual...supporting
confidence: 86%
“…Different authors suggest that treating spiders as a single group may mask effects and trends due to the diversity of shapes and habits among species (Cardoso et al, 2011;Szmatona-Túri et al, 2017;Muvengwi et al, 2018). Spiders are classified in eight different functional guilds, with variable life histories, according to their hunting strategies, such as active hunters and web weavers (Cardoso et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Among arthropod generalist predators, spiders have been one of the main focus in studies of grazing chronic disturbance (Macé et al 2019; Filazzola et al 2020). Despite some controversy and inconclusive results (Silva and Ott 2017; Muvengwi et al 2018; Samu et al 2018), authors usually suggest that ungrazing, low and moderate grazing may enhance spider diversity while heavy grazing reduce species richness and abundance, as well as species turnover (Szmatona-Túri et al 2017; Wang et al 2019; Ferreira et al 2020; Oyarzabal and Guimarães 2021). Moreover, grazing disturbance seems to affect spider guilds in opposite ways, where diversity of ground dweller spiders may be enhanced while orb-weaver spiders appear to be particularly sensitive to vegetation removal (Nogueira and Pinto-da-Rocha 2016; Neilly et al 2020), losing species richness in high grazing environments (Oyarzabal and Guimarães 2021).…”
Section: Introductionmentioning
confidence: 99%